2013
DOI: 10.1016/j.jconrel.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel bioerodible dexamethasone implant for uveitis and postoperative cataract inflammation

Abstract: Delivery of anti-inflammatory steroids concurrently to both anterior and posterior segments of the eye is a challenge. The anterior ocular structures limit topical delivery. Injection can be disproportionately and repeatedly invasive and selective for only one ocular hemisphere. We developed a novel implant that can compensate for the limited conveyance of topical medicine and reduce the repetitive invasiveness of injection from the capsular bag allowing dexamethasone (DXM) delivery to both the anterior and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…[5][6][7] As a result, high systemic doses and/or invasive therapies are used currently to treat a variety of conditions affecting the back of the eye, including sight-threatening diseases, such as age-related macular degeneration (AMD), diabetic retinopathy, and posterior uveitis. [8][9][10][11][12] High systemic dosing provides limited local exposure and duration of action, and often is associated with liabilities and drug-specific toxicities. [1][2] Intravitreal (IVT) injections provide the most direct method of delivery to the posterior tissues; however, IVT injections have the inherent potential for serious adverse events, such as retinal detachment, hemorrhage, endophthalmitis, and the development of cataracts.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] As a result, high systemic doses and/or invasive therapies are used currently to treat a variety of conditions affecting the back of the eye, including sight-threatening diseases, such as age-related macular degeneration (AMD), diabetic retinopathy, and posterior uveitis. [8][9][10][11][12] High systemic dosing provides limited local exposure and duration of action, and often is associated with liabilities and drug-specific toxicities. [1][2] Intravitreal (IVT) injections provide the most direct method of delivery to the posterior tissues; however, IVT injections have the inherent potential for serious adverse events, such as retinal detachment, hemorrhage, endophthalmitis, and the development of cataracts.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, implantation of the device can cause a small loss of vitreous amount, which act as a compensatory mechanism able to maintain lower values of IOP. Other intraocular dexamethasone-releasing devices used in previous studies have not been found to cause a significant IOP changes (FIAHO et al, 2006(FIAHO et al, , 2007CHENNAMANENI et al, 2013). However, a device containing fluocinolone acetonide has been reported to induce increase in IOP (BOLLINGER et al, 2011).…”
Section: Resultsmentioning
confidence: 94%
“…This consideration is clinically important because systemic steroid use is associated with many adverse effects. When an intraocular device is used, the systemic exposure to dexamethasone is extremely low (CHENNAMANENI et al, 2013). In fact, it is lower than when topical or systemic steroids are used (WEIJTENS et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Reports have indicated that the efficacy and safety of DEX for patients after cataract surgery and outcomes have showed DEX is potential drug for the prevention and treatment of retinal vein occlusion and non-infectious uveitis (18,19). In addition, DEX management decreased inflammation for uveitis and postoperative cataract inflammation (20). In this study, we investigated the ameliorative effects of DEX in decreasing AC inflammation compared to IND and CIP groups.…”
Section: Discussionmentioning
confidence: 97%